Note Purchase Agreement with Brazil. (Policy Papers; Policy Paper, 2010)
This Note Purchase Agreement (the "Agreement") is entered into between the Federative Republic of Brazil ("Brazil") and the International Monetary Fund (the "Fund"). Where specified in this Agreement, Banco Central do Brasil ("BCB") shall act as agent for Brazil in order to carry out the operations with the Fund herein described. In those cases, the Fund shall be entitled to consider any request, representation or notification from or to the BCB, or any consultation with the BCB, as constituting, respectively, a request, representation or notification from or to, or consultation with, Brazil.